Punishment Policy for Perpetrators of the Criminal Offenses of Accepting and Giving Bribes in the Republic of Kosovo - Hajdari, Azem; Hajdari, Albulena; Jupolli, Bashkim (Faculty of Law, Universitas Brawijaya, 2022)
This study examines the criminal offense of accepting and giving bribes as one of the oldest manifestations of corruption, which continues to be a critical issue even today. Furthermore, at a time when public opinion and perception of corruption in Kosovo are considered significant, this study aims to reflect the presence of these two criminal acts, reveal the fact that one of these offenses dominates, reveal the profiles of those convicted, and determine what punishment policy has been applied by courts. In addition, this study attempts to demonstrate the significant defiance, irregularities, and uncertainties that accompany prosecuting and adjudicating those who commit these types of offenses. This study has theoretical and practical implications as it addresses issues that, in various ways, are not adequately addressed in Kosovo and may perhaps go beyond Kosovo.